Analysis of markets for African leafy vegetables within Nairobi ant its environs and implications for on-farm conservation of biodiversity - Irungu, C.; Mburu, J.; Maundu, P.; Grum, M.; Hoeschle-Zeledon, I. (2007)
African Leafy Vegetables (ALVs) are important sources of essential macro and micro-nutrients. In addition they offer a source of livelihood when marketed, and also contribute to crop biodiversity. Despite these positive aspects, only a few ALVs are grown, marketed and consumed in Kenya. This study analyses the ALV market in Nairobi and the neighbouring areas, highlighting the factors that enable or inhibit its development. Furthermore, the study determined different factors influencing inter- and intra-specific on-farm biodiversity, with a focus on the role of ALV market development.